2015
DOI: 10.1111/jphp.12363
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone improves the kidney and liver changes induced by chronic cyclosporine A treatment and acute renal ischaemia/reperfusion in rats

Abstract: Kidney and liver injury due to CsA or renal I/R can be significantly reduced by TQ, which resets the oxidant/antioxidant balance of the affected organs through scavenging free radicals and antilipoperoxidative effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 31 publications
3
32
0
Order By: Relevance
“…Various studies have shown that TQ has protective effects against I/R injury to the several organs such as kidneys, lungs, and liver in different experimental models [38, 39]. The effect of TQ on hepatic and renal changes induced by renal I/R in the rats was investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have shown that TQ has protective effects against I/R injury to the several organs such as kidneys, lungs, and liver in different experimental models [38, 39]. The effect of TQ on hepatic and renal changes induced by renal I/R in the rats was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Farag et al [38] investigated the effects of chronic cyclosporine A (CsA) treatment and acute renal I/R on the liver and kidney in rats treated with TQ. TQ treatment (10 mg/kg per day) decreased serum indicators back to control levels and improved CsA-induced renal and hepatic histopathological alterations.…”
Section: Resultsmentioning
confidence: 99%
“…Hosseinzadeh et al showed that TQ has protective effects on lipid peroxidation after IRI in rat hippocampus (25). In various experimental studies, TQ's protective effects including antioxidant and free radical scavenging activity were shown (15)(16)(17). Additionally, TQ inhibits the some inflammatory mediators' production (26)(27)(28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Black seed is an annual flowering plant native to some areas like Mediterranean countries (13). 1963 was the year thymoquinone was first extracted as the main active ingredient of NS (14) and it was described as a potent superoxide scavenger and free radical (15)(16)(17). However, NS also has an antioxidative effect on the spinal cord, heart and renal tissue IRI (18)(19)(20).…”
Section: öZetmentioning
confidence: 99%
“…7 Since its rst extraction in 1963, 8 thymoquinone has been shown to act as a potent free radical and superoxide scavenger. [9][10][11] In addition, it has been shown to have anti-inammatory properties in vivo and vitro studies. 12,13 It has also been shown to exert positive effects on DOX-induced nephropathy and ischaemia-reperfusion-induced kidney injury in rats.…”
Section: Apoementioning
confidence: 99%